An Internal Calibration Approach of Multi-Channel SAR Sensors - Younis, Marwan; Adamiuk, Grzegorz; De Almeida, Felipe Queiroz; Huber, Sigurd; Jaeger, Marc; Loinger, Andrea; Martone, Michele; Rommel, Tobias; Krieger, Gerhard (ESA Advanced RF Sensors and Remote Sensing Instruments (ARSI), 2017)
Calibration methods of state-of-the-art spaceborne SAR are reviewed to suggest calibration strategies for future SAR systems. These systems will utilize digital beamforming, which poses new challenges for the calibration, as the increased complexity of multi-channel SAR does not allow for the extrapolation of current calibration techniques. Further, real-time error measurement and correction is unavoidable, which requires reconsidering current calibration approaches. One the other hand, the digital hardware already present in multi-channel SAR systems, offer opportunities for the calibration such as on-board error correction and digital calibration. This paper presents a calibration scheme suitable for multi-channel digital beam-forming SAR. The main characteristics of the suggested calibration concept is, that, it avoids the typical interruption of SAR operation when injecting the calibration signal –which would cause lost imaging pulses or a reduction in swath–, and that it allows for on-board channel correction. Internal calibration concepts do not measure errors outside the calibration signal path, such as the antenna, which thus cannot be corrected. These deficiencies are overcome by using a data driven calibration, meaning that the channel errors are extracted from the (raw) receive SAR data.
DLR Import::2019-04-03